Survey of plant-parasitic and entomopathogenic nematodes in vineyards of Quebec - Bélair, G.; Dauphinais, N.; Fournier, Y.; Mauléon, H. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2001)
A survey of plant-parasitic and entomopathogenic nematodes associated with vineyards was undertaken in the Estrie and Montérégie regions, the two major grapevine-producing areas in Quebec. Soil samples from 13 sampled vineyards were analyzed for the occurrence of plant-parasitic and entomopathogenic nematodes. Six genera of plant-parasitic nematodes were observed. The most commonly encountered plant-parasitic nematode genera were Pratylenchus and Paratylenchus, both occurring in 85% of sampled vineyards. No Xiphinema sp. were observed in surveyed vineyards. Entomopathogenic nematodes were recovered from 85% of the samples. Heterorhabditid and steinernematid nematodes were isolated from one and 11 vineyards respectively. Steinernematid isolates were identified as Steinernema carpocapsae.